The efficacy and safety of acupoint catgut embedding therapy for depression: a protocol for systematic review and meta-analysis - Li, Yadi; Zhou, Jianlong; Wei, Zheng; He, Xia; Liang, Lizhu; Sunzi, Kejimu (Frontiers in Psychiatry, 2024)
Background Depression is a common public health problem, characterized by persistent low mood, lack of pleasure and exhaustion. Conventional treatments such as antidepressants and psychotherapy have some limitations, including variable efficacy, adverse side effects and high costs. Acupoint catgut embedding (ACE) therapy, as a subtype of acupuncture, has gained increasing clinical application due to its long-term effects, higher patient compliance, and cost-effectiveness. This study aims to conduct a meta-analysis to evaluate the efficacy and safety of ACE for depression.Methods Electronic searches will be conducted in 12 databases (both in English and Chinese databases), encompassing from inception to April 2022, without language restrictions. Randomized controlled trials (RCTs) that involve ACE for treating depression will be included. The primary outcome measures will include the response rate, Hamilton Depression Rating Scale (HAMD), Beck Depression Inventory (BDI), and Traditional Chinese Medicine Symptom Scale (TCMSSS). The secondary outcome measure will include Quality of Life scale score (QoL) and the incidence of adverse events. Results will be presented as risk ratios for dichotomous data and mean differences for continuous data.Two reviewers will independently conduct study selection, data extraction, and quality assessment. The methodological quality of eligible studies will be evaluated according to the criteria specified by the Cochrane Handbook for Systematic Reviews of Interventions (Version 5.1.0). Meta-analysis will be performed by RevMan 5.3 software.Discussion Due to the limitations, a safer, high-efficacy and non-pharmacological intervention with minimal side effects is required for treating depression. ACE has the advantages of longer-lasting effects, improved patient compliance, and reduced treatment costs. This protocol represents a metaanalysis and systematic review, aiming to present the current evidence regarding the efficacy and safety of ACE for depression. It seeks to provide clinicians with a theoretical basis and valuable references for complementary and alternative medicine therapies in their treatment approaches.Systematic review registration PROSPERO registration number: CRD42022325966.